Dissociation in skin picking disorder and trichotillomania - Crisp, Zharia C.; Grant, Jon E. (Frontiers in Psychiatry, 2025)
IntroductionDissociation involves a lapse in normal perception of reality or awareness; it has Q6 been associated with multiple psychiatric disorders and has been suggested as a contributing factor in trichotillomania and skin picking disorder. This study aimed to explore the relationship between dissociation and trichotillomania and/or skin picking disorder. MethodsThree hundred and seventy adults with trichotillomania, skin picking disorder, or both (aged 18-65 years) were enrolled as part of an online survey. Participants completed a questionnaire on demographics, clinical characteristics, comorbidities, medications, and suicidality. Participants completed the Generic Body-Focused Repetitive Behaviors (BFRB) Scale-8 (GBS-8) and the Dissociative Experience Scale (DES). Regression analysis was used to examine the relationship between DES scores and GBS-8 scores, as well as clinical characteristics. ResultsDES scores significantly predicted GBS-8 impairment scores, suicidal ideation, non-suicidal self-injury, and suicide attempts. DiscussionDissociation may be either a driving force for many with hair pulling or skin picking, or pulling and picking may create a dissociative trance-like state. These findings suggest that dissociation is associated with greater impairment and worse clinical outcomes. Further research may elucidate whether there is benefit in treating dissociation in these patients.